COMMONWEALTH OF PORTORICO AS THE BASIS OF A PROPOSAL FOR A SOLUTION TO THE KOSOVO CONFLICT (Heritage, 2022)
According to the authors, the resolution of conflicts, such as the one in Kosovo, which has a long and complex history, must undoubtedly start from the real situation, while respecting the interests of all stakeholders and the balance of power domestically and internationally. In order to solve this problem, various ideas have been presented so far, mainly based on the experience of multicultural states that have used various contractual, constitutional and legal mechanisms to resolve conflicts of this kind. As possible models, the authors suggest the status of the Åland Islands, the Italian provinces of Trentino - South Tyrol and the Commonwealth of Puerto Rico. All three proposed models are a reflection of historical, legal-economic, sociological and cultural circumstances, so any consistent application by copying the solution to the status of Kosovo and Metohija would be doomed to failure from the very beginning. According to the author, starting from the real situation, and respecting the interests of all stakeholders, it is evident that the Puerto Rican Commonwealth model, with certain loans from the other two models and respect for local specifics, could be applicable to the Kosovo situation. According to this model, the Republic of Serbia would retain its sovereignty over Kosovo, while Kosovo would be recognized with limited international legal subjectivity, without membership in the United Nations and other important international organizations. The authors especially emphasize the importance of the model of South Tyrol, which could be a good starting point for regulating the status of the Serbian community, which in cooperation with the Brussels Agreement, called "Community of Serbian Municipalities" would have the status of autonomy within
Keywords: Alandi; Autonomy; South Tyrol; Commonwealth; Puerto Rico; Resolution 1244; Special status; Republic of Serbia; Constitution; United Nations